Boredom Proneness and Social Media Usage of College Students (American Journal of Human Psychology, 2024)
This descriptive-predictive study aimed to determine the correlation between the social media usage of college students and their boredom proneness in a University in Davao region. A total of 350 participants were chosen to participate in this study using simple random sampling techniques. A 22-item multidimensional state boredom questionnaire and 21-item social networking usage served as an instrument wherein the Jamovi was used for data analysis. The mean and standard deviation were utilized to test the level of both variables, and results showed that the level of social media usage and boredom proneness among students is high. The Shapiro-Wilk test was utilized to test the normality; it revealed that the data is not normally distributed. The Spearman rho correlation coefficient test revealed a significant relationship between social media usage and students’ boredom proneness, with a p-value of .001, indicating a strong positive correlation. Meanwhile, the result of Linear Regression showed 71% of the variance is explained by the three significant predictors contributing to the students’ social media usage which are Time Perception, Inattention and Disengagement. The study’s findings indicate that increased use of social media is associated with higher levels of boredom. In this case, school administration, local health authorities, and school counseling and guidance offices should enhance the implementation of policies regarding the responsible use of social media, integrate the findings into various programs, and increase public awareness of the effects of excessive social media use on people’s mental health and academic performance. Lastly, researchers should consider extending this topic with a quantitative approach and investigate the possible mediating factors between boredom and social media usage.